Inspektorat Bolaang Mongondow Selatan Dan Efektivitas Fungsinya Dalam Pencegahan Penyalahgunaan Dana Desa - Aditya Eka Prasetya Hasan; Erman I. Rahim; Abdul Hamid Tome (Jurnal Hukum dan Sosial Politik, 2024)
This research aims to (1) determine the Inspectorate's supervisory function in preventing misuse of Village Funds and (2) to analyze and formulate what factors influence the Inspectorate's function in carrying out its function as a supervisory element to prevent misuse of Village Funds in South Bolaang Mongondow Regency. This type of research is empirical research, namely research that examines community behavior that arises due to the existence of a legal rule, or vice versa, the formation of a legal rule due to behavior in society by conducting field research and literature review. The results of this research show that the prevention process carried out The Regional Inspectorate prevents misuse of Village Funds by supervising and controlling the management of Village Funds. Factors that influence its effectiveness are legal substance: There are no regional regulations or regent regulations regarding supervisory procedures. Legal structure: The number of auditors is still limited. Legal culture: An inspection process that does not fully reach the field. Where the law applies: There are 7 sub-districts and 83 villages in South Bolaang Mongondow Regency. Infrastructure: Limited facilities for mobilization and the absence of an online site as a source of information and public complaints. The research conclusion shows that the supervision carried out by the Regional Inspectorate of South Bolaang Mongondow Regency has not been effective.